The Relationship Between Discipline and Motivation on Mathematics Learning Outcomes of SMP Negeri 3 Pana Students - Trati Tappi; Hariani Harjuna; Inayanti Fatwa (Yayasan Ahmar Cendekia Indonesia, 2025)
This research uses quantitative methods. The data obtained were then analyzed with a series of statistical tests to examine the partial and simultaneous relationship between independent variables and the dependent variable. The t-test results show that learning discipline has a positive and significant relationship with Mathematics learning outcomes, with a correlation coefficient of 0.762 and a significant value (Sig.) of 0.000. In addition, learning motivation also has a positive and significant relationship with Mathematics learning outcomes, with a correlation coefficient of 0.726 and a significant value (Sig.) of 0.000. Simultaneously, the F test results show that learning discipline and learning motivation together have a positive and significant relationship with Mathematics learning outcomes, with a calculated value of 38.668 and a significant value (Sig.) of 0.000. Thus, it can be concluded that there is a positive and significant relationship between learning discipline and Mathematics learning outcomes, as well as between learning motivation and Mathematics learning outcomes. Simultaneously, the relationship between learning discipline and learning motivation with Mathematics learning outcomes is also positive and significant. This means that the higher the learning discipline and learning motivation of students, the higher the mathematics learning outcomes achieved.